Gender Preference, Attitude and Awareness of Young Eligible Couples Towards Pre Natal-Sex Determination in Lucknow District - Srivastava, Ashish; Singh, Jai V; Singh, Om P; Singh, Vijay K; Singh, Neelam (National Journal of Community Medicine, 2014)
Background: Falling sex ratio is a major concern. Gender preference of young couples, their attitude towards pre natal sex determination and awareness regarding related social issues plays an important role in determining their practice and needs to be studied. Materials and Methods: This was a cross-sectional; community based descriptive study conducted in Lucknow district from August, 2012 to April, 2013. Couples were interviewed using a pre tested, semi structured questionnaire. Gender preference was assessed using the Coombs scale and attitude towards pre natal sex determination was elicited with the help of a case study. Multi stage random sampling technique was adopted to select the couples. A total of 308 couples were interviewed. Results: Son preference was observed among 64.6% of the couples while 28.1% couples were in favour of pre natal sex determination. Overall 72.1% couples were aware of unfavourable sex ratio in the country and 74.7% were aware of the harmful effects of declining sex ratio on the society. Majority (93.2%) knew that pre natal sex determination is a crime but only 1.6% were aware of the punishment for the offence. Conclusion: The study clearly shows that son preference and pre natal sex determination still finds favour with a substantial proportion of young couples and emphasises the need for proper counselling and behaviour change communication among them.